Menelaah Perkembangan Kajian Hisab Rukyah di Indonesia - Zulhadi, Heri (UIN ALAUDDIN MAKASSAR, 2019)
Abstract Hisab and rukyah are two methods of study used by Muslims to determine the start time of prayer, fasting, hajj and so forth. Periodesasi hisab rukyah, at a glance must have imagined what is meant by hisab rukyah. In the discourse about the Hijri calendar known by the term hisab and rukyah. Hisab is a calendar calculation system based on the average circulation of the moon that surrounds the earth and is conventionally defined. This reckoning system began since the establishment of Caliph Umar ibn Khattab ra (17H) as a reference for composing an enduring Islamic calendar. Another opinion says that this calendar system started in 16 H or 18 H, but the more popular is the year 17 H. While Rukyah is seeing the hilal directly with the naked eye or with the help of tools such as telescopes or other tools that support to see the new moon every end of Qamariyah month. The word rukyah is more famous as rukyatul hilalyaitu see moon. In this study, the author will describe a little about the history of hisab and rukyah in the period of prophets, companions, tabi'in, mid to modern period today. In this study, the scope of hisab rukya includes prayer times, Qibla direction, the beginning of Qamariyah month, eclipse and hijri calendar. Keyword: Hisab, Rukyah.